Effects of age and tissue of Juniperus sabina L. on its phytochemical characteristics, anti-cholinesterase, antidiabetes, and anti-drug resistant bacteria activities - Xu, Shengnan; Chen, Qian; Luo, Na; Yang, Jinyan; Li, Dengwu (Frontiers in Plant Science, 2023)
Juniperus sabina L. is used in the traditional Chinese medicine (TCM) system to prevent or treat various diseases. However, only the leaves and branches are used as medicinal parts. The aim of this study was to compare the chemical characteristics of different tissues (leaves, branches, stems, and roots) of J. sabina at different ages by HPLC-MS and to evaluate the biological activity (enzyme inhibition, anti-drug-resistant bacteria). Total phenol (TPC) and total lignan (TLC) contents in J. sabina were determined by Folin-Ciocalteu method and UV spectrophotometry, respectively. High levels of total phenols (87.16 mg GAE/g dry weight) and total lignans (491.24 mg PPT/g dry weight) were detected in fifteen annual J. sabina roots and current year leaves, respectively. Eleven compounds, of which six were phenolic compounds and five were lignans, were identified and quantified by HPLC/HPLC-MS. Statistical analysis showed that the distribution and content of the detected compounds showed considerable variation among ages and tissues, and that the current year leaves of fifteen annual J. sabina could be used as a potential application site for the source of podophyllotoxin. Acetylcholinesterase (AChE) inhibitory activity was found to be the highest on the extracts of fifteen annual J. sabina current year leaves (47.37 μg/mL), while the highest inhibition towards butyrylcholinesterase (BChE) was observed for the extracts of seven annual J. sabina previous year leaves (136.3 μg/mL). And the second annual J. sabina current year stem's extracts showed the best antidiabetic activity (anti-α-glucosidase, 62.59 μg/mL). In addition, the extracts of fifteen annual J. sabina roots (47.37 μg/mL) showed the highest anti-MRSA activity (31.25 μg/mL). Redundancy analysis (RDA) was conducted to clarify the factors affecting the biological activity of J. sabina, and its results showed that epicatechin and matairesinol showed positive promotion. This study provides a new perspective for understanding the chemical differences and comprehensive utilization of different tissues of J. sabina.